3abc+5bc-6ac,-7abc-9bc,Subtract the given terms.
Answers
Answered by
0
BONJOUR,
❤ ❤ ❤ ❤
![(3abc + 5bc - 6ac) - ( - 7abc - 9bc) \\ 3abc + 5bc - 6ac + 7abc + 9bc \\ 10abc + 14bc - 6ac (3abc + 5bc - 6ac) - ( - 7abc - 9bc) \\ 3abc + 5bc - 6ac + 7abc + 9bc \\ 10abc + 14bc - 6ac](https://tex.z-dn.net/?f=%283abc+%2B+5bc+-+6ac%29+-+%28+-+7abc+-+9bc%29+%5C%5C+3abc+%2B+5bc+-+6ac+%2B+7abc+%2B+9bc+%5C%5C+10abc+%2B+14bc+-+6ac)
❤ ❤ ❤ ❤
Answered by
0
Solution :
Given two expressions are ,
First expression = 3abc+5bc-6ac,
Second expression = -7abc-9bc
i ) Subtracting second expression from
first , we get
3abc + 5bc - 6ac - ( -7abc - 9bc )
= 3abc + 5bc - 6ac + 7abc + 9bc
= 3abc + 7abc + 5bc + 9bc - 6ac
= ( 3 + 7 )abc + ( 5 + 9 )bc - 6ac
= 10abc + 14bc - 6ac
ii ) Subtracting first expression from
second , we get
- 7abc - 9bc - ( 3abc + 5bc - 6ac )
= -7abc - 9bc - 3abc - 5bc + 6ac
= -7abc - 3abc - 9bc - 5bc + 6ac
= ( -7 - 3 )abc + ( -9 - 5 )bc + 6ac
= -10abc - 14bc + 6ac
••••
Given two expressions are ,
First expression = 3abc+5bc-6ac,
Second expression = -7abc-9bc
i ) Subtracting second expression from
first , we get
3abc + 5bc - 6ac - ( -7abc - 9bc )
= 3abc + 5bc - 6ac + 7abc + 9bc
= 3abc + 7abc + 5bc + 9bc - 6ac
= ( 3 + 7 )abc + ( 5 + 9 )bc - 6ac
= 10abc + 14bc - 6ac
ii ) Subtracting first expression from
second , we get
- 7abc - 9bc - ( 3abc + 5bc - 6ac )
= -7abc - 9bc - 3abc - 5bc + 6ac
= -7abc - 3abc - 9bc - 5bc + 6ac
= ( -7 - 3 )abc + ( -9 - 5 )bc + 6ac
= -10abc - 14bc + 6ac
••••
Similar questions